William Fellner. Modern economic analysis. Nueva York : McGraw-Hill, 1960. xiv, 459 p. - Suárez, Eduardo L. (Estudios Demográficos y Urbanos, 1968)
WILLIAM FELLNER, Modern Economic Analysis. Nueva York, McGraw-Hill, 1960.